2015
DOI: 10.1007/s00343-015-4333-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiated Ergosan on the growth performance and mucus biological components of rainbow trout Oncorhynchus mykiss

Abstract: Eff ects of irradiated and non-irradiated Ergosan extract (alginic acid) on rainbow trout growth performance and skin mucosal immunity were compared. Ergosan was irradiated at 30 kGy in a cobalt-60 irradiator. A total of 252 fi sh (128.03±9.4 g) were randomly divided into four equal groups, given the basal diet either unsupplemented with Ergosan (control group) or supplemented with crude Ergosan (5 g/kg), ethanol-extracted Ergosan (0.33 g/kg) or irradiated Ergosan (0.33 g/kg) according to this protocol: basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For example, γ-irradiation of feed with 20% soybean meal improved protein digestibility and increased growth in fighting fish (Betta splendens) [38]. Rainbow trout (Oncorhynchus mykiss) also showed a higher uptake of γ-irradiated Ergosan in the intestine compared to crude Ergosan, which resulted in improved growth performance [39]. More recently, it was revealed that the use of γ-irradiated propolis extract at 10 and 30 kGy in the diet of common carp (Cyprinus carpio) boosted growth rates [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, γ-irradiation of feed with 20% soybean meal improved protein digestibility and increased growth in fighting fish (Betta splendens) [38]. Rainbow trout (Oncorhynchus mykiss) also showed a higher uptake of γ-irradiated Ergosan in the intestine compared to crude Ergosan, which resulted in improved growth performance [39]. More recently, it was revealed that the use of γ-irradiated propolis extract at 10 and 30 kGy in the diet of common carp (Cyprinus carpio) boosted growth rates [40].…”
Section: Discussionmentioning
confidence: 99%
“…There have been few works carried out to study the effects of irradiated feed additives in fish mucosal immunity. For example, γ-irradiated alginic acid boosted skin mucosal immunity and resistance to crowding stress in rainbow trout [39,45]. Feeding with date fruit extract also increased mucosal immune parameters (lysozyme, protease and alkaline phosphatase activity) in common carp fry skin [16].…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and twenty-five ( 225) parasite free fish were randomly allocated into 5 groups in triplicate at a density of 15 fish per aquarium, equipped with biological filtration. The vaccine dose rate was 100 gamma-irradiation trophonts per 150 gram fish body weight (via the bath method) (SHEIKHZADEH et al, 2016). The1 st group was immunized with 100 gamma-irradiation (170 Gray) inactive trophonts, the 2 nd group immunized with alginate nanoparticles, the 3 rd group immunized with10,000 live trophonts (as the positive control group), and the 4 th group was the negative control (uninfected rainbow trout).…”
Section: Methodsmentioning
confidence: 99%